Kemampuan Penyerapan dan Reduksi Lengas Tanah Pada Media Polybag Kombinasi Tanah dan Kompos: Soil Moisture Absorption dnd Reduction Capability In Polybag Media Combination of Soil and Compost - I Dewa Gede Jaya Negara; Salehudin Salehudin; Suparjo Suparjo; Anid Supriyadi; Humairo Saidah; Lalu Dwiki Axela Andriawan (LPPM Universitas Mataram, 2023)
Soil moisture is an important factor needed by plants for growth, and therefore the amount of soil moisture that can be stored depends on the type of soil or the composition of the soil-forming materials. Compost is one of the nutrients that is often used in the manufacture of planting media on land in the form of polybags, and the amount of compost composition on the soil is thought to greatly affect the ability to store water in the media. This study aims to test drip irrigation on a mixture of compost and soil on storage of irrigation water. Tests were carried out at a ratio of 70%: 30%, 50%: 50% and 30%: 70%. Irrigation was tested at a duration of 5 minutes, 10 minutes, and 15 minutes, and the data analyzed included irrigation distribution data, discharge, soil moisture data (w) and daily soil moisture change data. The results of the analysis are presented in the form of tables and graphs, then discussed and concluded descriptively. The results of the analysis show that the flow rate obtained is greater if the difference in water level to the land is greater, and the average Cu value obtained is 95.79% which is very good. With initial soil moisture in the range of 19%-25, soil moisture gain obtained by drip irrigation for 5 minutes -10 minutes is around 12%, and for a duration of 15 minutes soil moisture gain is obtained by 8% -21%. The lowest recharge was obtained on land with 30% soil and 70% compost of 8%-12%. The amount of soil moisture reduction after 24 hours of irrigation test was 6% - 17%, the lowest reduction was at 70% compost and 30% soil around 6%.